A newly developed patient fixation system using a dedicated mouthpiece and dental impression materials for head and neck radiotherapy: a preliminary study. (11th July 2022) - Sakamoto, Masataka; Konishi, Kenta; Ohira, Keiichi; Hirata, Masanori; Wakabayashi, Kohei; Aramaki, Shuhei; Kokubo, Ryo; Nakamura, Katsumasa
Abstract: We evaluated the basic characteristics and efficacy of our newly developed patient fixation system for head and neck radiotherapy that uses a dedicated mouthpiece and dental impression materials. The present investigation demonstrated that with this system, the changes in the absorbed dose to water depending on the material of the mouthpiece were small, with a maximum of 0.32% for a 10-MV photon beam. For the dental impression material, we selected a silicone material with the lowest Hounsfield unit (HU) value that had little effect on the generation of artifacts and the quality of the X-ray beam. Multiphase magnetic resonance imaging (MRI) revealed that the head-up and -down motions in the thermoplastic shell without the mouthpiece were 5.76 ± 1.54 mm, whereas the motion with the mouthpiece decreased significantly to 1.72 ± 0.92 mm ( P = 0.006). Similarly, the head-left and -right motion displacement decreased from 6.32 ± 1.86 mm without the mouthpiece to 1.80 ± 0.42 mm with the mouthpiece ( P = 0.003). Regarding the tongue depressor function of the mouthpiece, the median distance from the hard palate to the surface of the tongue was 28.42 mm. The present results indicate that the new immobilization device developed herein that uses a mouthpiece and a thermoplastic shell is useful for suppressing patients' head motions and tongue positions.